Characteristics of migrant entrepreneurs: Asset in times of crisis? - Alexandra David; Susann Schäfer; Judith Terstriep (Institut Arbeit und Technik (IAT), 2021)
We identified three major characteristics of migrant entrepreneurs at the individual and organisational level: risk-taking and bricolage attitude, making extensive use of social and cultural capital, and transnational embeddedness. Perseverance and creativity not only prompt entrepreneurs to set up a business faster but possibly better cope with exogenous shocks and resulting uncertainty. Being embedded and acting in various transnational and socio-cultural settings allows them to access additional resources, including specific knowledge, experiences, and cultures, to use for business stabilisation. Based on concrete experiences of crises at the time of flight or migration specific behaviours and virtues emerge that may have a lasting impact on understanding and dealing with wicked situations such as the COVID-19 crisis. The joint project ReCOVery - Resilience of Migrant Entrepreneurs during the COVID-19 crises centres on the ability of migrant entrepreneurs to cope with the current crisis.
Keywords: 330